2019
DOI: 10.1101/600189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional analysis defines TCR and cytokine-stimulated MAIT cells as rapid polyfunctional effector T cells that can coordinate the immune response

Abstract: 8 9 3 1human MAIT cells to TCR and cytokine stimulation. We report that MAIT cells rapidly respond 3 2 to TCR stimulation through the production of multiple effector cytokines and chemokines, 3 3 alteration of their cytotoxic granule content and transcription factor expression, and upregulation 3 4 of co-stimulatory proteins CD40L and 4-1BB. In contrast, cytokine-mediated activation is slower 3 5and results in more limited production of cytokines, chemokines, and co-stimulatory proteins; 3 6 differences in gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 69 publications
2
17
0
Order By: Relevance
“…Intriguingly, at this early time point, perforin expression appears to be completely dependent on T1-IFNs. This is consistent with two previous studies that show TCR-independent perforin production by MAIT cells activated by E. coli for 6 and 24 hours (Kurioka et al, 2015; Lamichhane et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Intriguingly, at this early time point, perforin expression appears to be completely dependent on T1-IFNs. This is consistent with two previous studies that show TCR-independent perforin production by MAIT cells activated by E. coli for 6 and 24 hours (Kurioka et al, 2015; Lamichhane et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…Bacteria can provide both MR1 ligand and co-stimulatory signals leading to robust activation of MAIT cells (Chen et al, 2017; Ussher et al, 2016). Recently, we reported that various innate signalling pathways, including IFNα/β signalling, were enriched early in MAIT cells upon stimulation with E. coli compared to activation with 5-A-RU alone (Lamichhane et al, 2019). Therefore, we activated MAIT cells with E. coli for 6 hours with or without B18R to assess the role of T1-IFNs during early MAIT cell activation by a riboflavin synthesising bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations